Ecological Index and Distribution of Sponges (Porifera) in the Waters of Labuan Beropa Village, South Konawe - Sipayung, Putri Pebrina; Afu, La Ode Alirman; Rahmadani, Rahmadani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Tropical coastal ecosystems possess high biodiversity and play a vital role in maintaining ecological functions, supported in part by the presence of sponges (Porifera) as filter feeders. This study aimed to identify species diversity, calculate ecological indices, and analyze the distribution patterns of sponges in the coastal waters of Labuan Beropa, South Konawe. Field surveys were conducted through sponge sampling at several observation sites, followed by taxonomic identification, calculation of Shannon-Wiener diversity index (H’), evenness (E), dominance (C), and distribution pattern analysis using the Morisita index. Seven benthic sponge species were recorded: Aaptos pernucleata, Aaptos suberitoides, Clathria (thalysias), Haliclona cymaeformis, Hyrtios erectus, Mycale sp., and Xestospongia muta. The highest density occurred in areas with stable rocky substrates, calm currents, and low anthropogenic disturbance, while the lowest density was observed in areas with intense human activities. H’ values were low (0.632–0.735), E values were high (0.748–0.869), and C values were low (<0.3). Distribution patterns were predominantly clumped, with some species exhibiting uniform or random patterns. These findings indicate that habitat physical quality and the degree of anthropogenic pressure are key determinants of sponge community structure. The baseline data generated can be used to support sustainable management and conservation of tropical coastal ecosystems.